How do different micro-mobility vehicles affect longitudinal control? Results from a field experiment. (February 2023) - Dozza, Marco; Li, Tianyou; Billstein, Lucas; Svernlöv, Christoffer; Rasch, Alexander
Highlights: 34 participants rode a bike, an e-bike, an e-scooter, and a Segway in field trials. We collected acceleration and braking maneuvers from in-vehicle sensors and LiDAR. Micromobility behavior is predictable and different across vehicle types. We propose models for the prediction of micromobility kinematics. Active safety and automated driving may benefit from these models. Abstract: Introduction: While micromobility vehicles offer new transport opportunities and may decrease fuel emissions, the extent to which these benefits outweigh the safety costs is still uncertain. For instance, e-scooterists have been reported to experience a tenfold crash risk compared to ordinary cyclists. Today, we still do not know whether the real safety problem is the vehicle, the human, or the infrastructure. In other words, the new vehicles may not necessarily be unsafe; the behavior of their riders, in combination with an infrastructure that was not designed to accommodate micromobility, may be the real issue. Method: In this paper, we compared e-scooters and Segways with bicycles in field trials to determine whether these new vehicles create different constraints for longitudinal control (e.g., in braking avoidance maneuvers). Results: The results show that acceleration and deceleration performance changes across vehicles; specifically, e-scooters and Segways that we tested cannot brake as efficiently as bicycles. Further, bicycles are experienced as more stable, maneuverable, and safe than Segways and e-scooters. We also derived kinematic models for acceleration and braking that can be used to predict rider trajectories in active safety systems. Practical Applications: The results from this study suggest that, while new micromobility solutions may not be intrinsically unsafe, they may require some behavior and/or infrastructure adaptations to improve their safety. We also discuss how policy making, safety system design, and traffic education may use our results to support the safe integration of micromobility into the transport system.